Investigating the Effect of an Anti-Inflammatory Drug in Determining NURR1 Expression and Thus Exploring the Progression of Parkinson's Disease - Zheng, X; Zhao, Z; Zhao, L (Physiological research, 2024)
Nonsteroidal anti-inflammatory drugs are the most widely used drugs for Parkinson's disease (PD), of which ibuprofen shows positive effects in suppressing symptoms; however, the associated risk needs to be addressed in different pathological stages. Initially, we developed an initial and advanced stage of the Parkinson disease mouse model by intraperitoneal injection of MPTP (20 mg/kg; 1-methyl-4-phenyl-1,2,3,6-tetrahydro-pyridine) for 10 and 20 days, respectively. Subsequently, ibuprofen treatment was administered for 2 months, and a pole test, rotarod test, histology, immunohistochemistry, and western blotting were performed to determine neuronal motor function. Histological analysis for 10 days after mice were injected with MPTP showed the onset of neurodegeneration and cell aggregation, indicating the initial stages of Parkinson's disease. Advanced Parkinson's disease was marked by Lewy body formation after another 10 days of MPTP injection. Neurodegeneration reverted after ibuprofen therapy in initial Parkinson's disease but not in advanced Parkinson's disease. The pole and rotarod tests confirmed that motor activity in the initial Parkinson disease with ibuprofen treatment recovered (p<0.01). However, no improvement was observed in the ibuprofen-treated mice with advanced disease mice. Interestingly, ibuprofen treatment resulted in a significant improvement (p<0.01) in NURR1 (Nuclear receptor-related 1) expression in mice with early PD, but no substantial improvement was observed in its expression in mice with advanced PD. Our findings indicate that NURR1 exerts anti-inflammatory and neuroprotective effects. Overall, NURR1 contributed to the effects of ibuprofen on PD at different pathological stages.
Keywords: ibuprofen; modely nemocí na zvířatech; neuroprotektivní látky; dopaminergní neurony; Neuroprotective Agents; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine; Animals; Ibuprofen; zvířata; 1-methyl-4-fenyl-1,2,3,6-tetrahydropyridin; myši inbrední C57BL; Disease Models, Animal; myši; Dopaminergic Neurons; Mice, Inbred C57BL; antiflogistika; Anti-Inflammatory Agents; Mice; Parkinson Disease; Parkinsonova nemoc